Neo-liberal Subjectivity, Self-branding and ‘My Rape Story’ YouTube Videos - Harrington, Carol (Critical sociology, 2019)
This article considers the YouTube ‘My Rape Story’ genre in light of critical feminist analyses of rape survivor stories. The feminist mobilization that developed out of the political ferment of 1968 told a ‘rape story’ of male power and women’s oppression. However, as first-hand rape stories proliferated in late 20th-century popular media, psychological experts typically framed them with therapeutic narratives of individual self-efficacy and self-transformation. Critical feminist analyses of such rape ‘survivor discourse’ called for new discursive spaces that would allow survivors to eschew therapeutic accounts. A new generation of women have spoken out on a variety of digital platforms, confronting established limits on talking about rape. Considering YouTube ‘My Rape Story’ videos as one manifestation of this new wave of speaking out, my analysis shows that examples of such videos evidence the impact of incitements to self-disclosure through self-branding built into much social media. I argue that these videos exemplify how first-hand rape stories can provide a site for the construction of neo-liberal subjectivity by positioning rape trauma as something survivors must work on in order to achieve self-efficacy. Nevertheless, these accounts also show resistance to victim-blaming rape myths.